2022
DOI: 10.1155/2022/8374471
|View full text |Cite
|
Sign up to set email alerts
|

Water Removal from an Ethanol-Water Mixture at Azeotropic Condition by Adsorption Technique

Abstract: The separation of ethanol-water mixture is employed in the present work to produce pure ethanol, the present investigation on the separation of water from the ethanol to achieve pure ethanol by adsorption process. The different parameters like quantity of adsorbent, flow rate of feed mixture, and different adsorbents which are zeolite 3A, zeolite 4A, and silica gel are selected to study purification of ethanol by adsorption. The effect of process parameter for purification is also recorded and studied to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…When comparing the first and fifth cycles, the adsorption ability of BMB500 only dropped significantly below 60% after the fourth cycle. The decrease in the adsorption capacity of the BMB500 after each desorption experiment can be ascribed to the loss of functional groups on the BMB500's surface [46]. The result of these experimental findings showed that the adsorbent (BMB500) had good regeneration efficiency for the first four cycles and could be successfully re-used four times.…”
Section: Reusability Of the Ball-milled Biocharmentioning
confidence: 93%
See 1 more Smart Citation
“…When comparing the first and fifth cycles, the adsorption ability of BMB500 only dropped significantly below 60% after the fourth cycle. The decrease in the adsorption capacity of the BMB500 after each desorption experiment can be ascribed to the loss of functional groups on the BMB500's surface [46]. The result of these experimental findings showed that the adsorbent (BMB500) had good regeneration efficiency for the first four cycles and could be successfully re-used four times.…”
Section: Reusability Of the Ball-milled Biocharmentioning
confidence: 93%
“…In each cycle of the adsorption-desorption test, the recycled ball-milled biochar was added to 25 mL of 2 mg/L mixed solutions of the steroidal hormones. The adsorption process was then repeated five times to assess the efficiency of the regenerated ball-milled biochar [46,47].…”
Section: Regeneration Experimentsmentioning
confidence: 99%
“…The sensitivity of columns in PSD is presented in Figure 5. Results imply that more stages in the 1 st distillation column lead to the asymptotic condition of bioethanol concentration at approximately 96% due to the azeotropic phenomenon 35) . Likewise, the greater actual stages in the 2 nd column reflect the intensive cost that should be required to rectify bioethanol from 96% to 99.96%.…”
Section: Downstream Processing Sectionmentioning
confidence: 94%
“…Nevertheless, it is still rarely communicated as nowadays only contains a total of 49 documents, as seen in Figure 1. The aforementioned list of studies is dominant in experimental mode focusing on hydrolysis, fermentation, or ethanol distillation separately [32][33][34][35] . Thus, a more specialized and integrated simulation study in corn cob sustainable valorization by fermentation using Zymomonas mobilis to produce bioethanol is believed to fill the gap and contribute to science and technology communities.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, zeolite 3A and calcium oxide were used as adsorbents because both adsorbents were effective in producing fuel-grade ethanol. Based on the research of Mekala et al (2022), Zeolite 3A is a better adsorbent and is also effective for absorbing water in an ethanolwater mixture under azeotropic conditions when compared to zeolite 4A. The highest concentration obtained was 99.9443% using zeolite 3A as adsorbent.…”
Section: Introductionmentioning
confidence: 99%